2010
DOI: 10.1364/ao.49.005067
|View full text |Cite
|
Sign up to set email alerts
|

Electronic speckle pattern interferometry and digital holographic interferometry with microbolometer arrays at 106 μm

Abstract: Electronic speckle pattern interferometry and digital holographic interferometry are investigated at long infrared wavelengths. Using such wavelengths allows one to extend the measurement range and decrease the sensitivity of the techniques to external perturbations. We discuss the behavior of reflection by the object surfaces due to the long wavelength. We have developed different experimental configurations associating a CO(2) laser emitting at 10.6 μm and microbolometer arrays. Phase-shifting in-plane and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…However, Maack et al [25] have already shown that ESPI can be performed under such circumstances. Their works were carried out under visible light, and we extended this discussion in our earlier works to LWIR ESPI [21].…”
Section: Lwir Electronic Speckle Pattern Interferometrymentioning
confidence: 89%
See 2 more Smart Citations
“…However, Maack et al [25] have already shown that ESPI can be performed under such circumstances. Their works were carried out under visible light, and we extended this discussion in our earlier works to LWIR ESPI [21].…”
Section: Lwir Electronic Speckle Pattern Interferometrymentioning
confidence: 89%
“…Recently we have proposed several setups using electronic recording of holograms and specklegrams with microbolometer arrays and a CO 2 laser for applications in interferometry of scattering objects, more specifically in-plane displacement measurements by ESPI [20] and out-of-plane displacement by both ESPI and lensless digital HI (DHI) [21]. The results presented there were obtained with early microbolometer technologies with small formats (320 × 240 pixels) and with the purpose of demonstrating the capabilities of LWIR holography techniques in applications of displacement measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular it allows observing large objects and in metrology it allows measuring large displacements while rendering holography more immune to environmental perturbations, compared to holography in the visible. For metrology we demonstrated various holographic techniques in LWIR: speckle interferometry [2,4], DH interferometry [2][3][4] and shearography [4]. The LWIR holographic set-up generally makes use of microbolometer arrays based thermal imagers.…”
Section: Introductionmentioning
confidence: 99%
“…In particular it allows observing large objects due to the fact that at such wavelengths the ratio between the wavelength and the pixel size allows reconstructing objects 5 to 10 times larger than with DH in visible light [2,3]. We already presented various configurations of LWIR DH interferometry and electronic speckle pattern interferometry for deformation metrology and non destructive testing [3,4]. In this paper we present the application of LWIR DH in interferometric testing of large deformation of large aspheric mirrors in the frame of a European Space Agency project.…”
mentioning
confidence: 99%